1991
DOI: 10.21273/jashs.116.3.435
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Sodium Irradiation and Infrared Radiation Accelerate Petunia Seedling Growth

Abstract: The increase in photosynthetic photon flux (PPF) and plant temperature associated with supplemental high pressure sodium (HPS) irradiation were investigated during Petunia × hybrids Villm. `Red Flash' seedling development. Seedlings were treated for 14 days following emergence or 5 days after the first true leaf had expanded to 1 mm. Treatments consisted of continuous infrared (IR) radiation (Ambient + IR), ambient conditions with spill-over radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Developmental rates, including leaf unfolding, are influenced by temperature. SL increased root zone and leaf temperature (Graper and Healy, 1991) and shoot-tip temperature of plants (Faust and Heins, 1997). In Season I of this study, HPS lighting at 90 mmolÁm -2 Ás -1 increased media temperature by 2.4°C, which may partially explain the acceleration of germination by %1 d (data not shown).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Developmental rates, including leaf unfolding, are influenced by temperature. SL increased root zone and leaf temperature (Graper and Healy, 1991) and shoot-tip temperature of plants (Faust and Heins, 1997). In Season I of this study, HPS lighting at 90 mmolÁm -2 Ás -1 increased media temperature by 2.4°C, which may partially explain the acceleration of germination by %1 d (data not shown).…”
Section: Discussionmentioning
confidence: 60%
“…Faust and Heins (1997) reported that Catharanthus roseus exposed to supplemental light from HPS lamps at 50, 75, and 100 mmolÁm -2 Ás -1 were 1.2, 1.5, and 1.7°C warmer, respectively, than plants in darkness. HPS SL for 24 h at 160 mmolÁm -2 Ás -1 increased media and plant temperature by 3.6 and 4.3°C, respectively, and the fresh weight of petunia seedlings by 88% at 12 d after treatment (Graper and Healy, 1991). Elevating media and plant temperature (+3.6 and +4.8°C, respectively) without increasing the PPF by using infrared (IR) lamps increased fresh weight by 38%, and HPS lighting removing IR radiation increased fresh weight by 68%, elevating media and leaf temperature by 2.0 and 2.5°C, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Biomass accumulation in seedling-plant or rooted cuttings of annual bedding plants tends to be positively correlated with light intensity or daily light integral (DLI) levels during propagation [18,19]. Growth and quality of rooted cuttings of the herbaceous annual plants can be increased by increasing the DLI after callusing under a DLI of 5 mol m −2 d −1 [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas increasing DLI increased the leaf number of cilantro and dill, and EC had no effect, nutrient solution EC interacted with DLI to affect the unfolded leaf number for parsley. Temperature increases with increased radiation [20], especially with high-pressure sodium lamps [21,22], which were used in this experiment. Though plant temperatures were not measured in the present study, the minimal increase in leaf number with increasing DLI for dill and parsley could likely be attributed to this effect.…”
Section: Discussionmentioning
confidence: 99%